52. EVALUATION OF SURGICAL OUTCOMES OF INTRAOCULAR LENS FIXATION FOR TRAUMATIC LENS INJURY IN CHILDREN (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the surgical outcomes of intraocular lens (IOL) fixation using theYamane technique for the treatment of traumatic crystalline lens injury in children.Subjects and Methods: A descriptive, prospective, uncontrolled study was conducted on30 eyes of 30 pediatric patients (≤15 years) who underwent sutureless IOL fixation with theYamane technique at the Vietnam National Eye Hospital from January 2020 to July 2025.Data were collected preoperatively and at 1 week, 1 month, and 3 months postoperatively,including baseline patient characteristics, lens status, surgical complications, and overallsurgical outcomes.Results: At 3 months after surgery, 86.7% of eyes achieved good outcomes and 13.3%achieved fair outcomes. Mean best-corrected visual acuity (BCVA) improved significantly,with logMAR BCVA increasing from 1.52 preoperatively to 0.63 at 3 months (p
Keywords: Intraocular Lens (IOLs) Fixation, Yamane technique, children, ocular trauma, lens injury